F(x) = -3(x-1) find f(o).
2 answers:
Answer:
f(0) = 3
Step-by-step explanation:
f(x) = -3(x-1)
Put x as 0 and solve.
f(0) = -3(0-1)
Solve the brackets.
f(0) = -3(-1)
Multiply both terms.
f(0) = 3
Answer:
f(0) = 3
Step-by-step explanation:
Step 1: Distribute
f(x) = -3x + 3
Step 2: Plug in
f(0) = -3(0) + 3
f(0) = 3
You might be interested in
The lines mean that they are parallel
Answer:670
Step-by-step explanation:
200 + 500 - 30 =
700-30
670
<span>a rectangle of dimensions 1 cm * 50 cm has a perimeter of 102 cm.</span>
8 alligator because is u divide 48/5 you get 40 and the remaining that r awake is 8
Jamie get back:5-1.15
=$3.85